Factors Controlling the Hydraulic Fracture Trajectory in Unconventional Reservoirs - Peng Zheng; Erhu Liu; Desheng Zhou; Xinwei Du; Zhongjun Ma (Geofluids)
The morphology of hydraulic fracture is affected by many factors. In previous studies, due to the heterogeneity of rock samples and the limitations of sample size, influence degree of various factors on fracture deflection angle has not been well distinguished in laboratory experiments. Based on the boundary element method, we established a mathematical model to study the factors controlling the morphology of hydraulic fracture. Simulation results show that with increasing injection pressure, the radius of the fracture curvature increases. When the difference between the injection pressure and the maximum principal stress is 5 times the ground stress difference, the influence of in situ stress on hydraulic fracture deflection can be ignored. Hydraulic fracture deflection angle was relatively larger when considering the viscosity of the fracturing fluid. When stress difference is too small or the injection pressure is too big, the deflection angle of fracture is easy to fluctuate during initial propagation. Too large Young’s modulus and too small Poisson’s ratio will inhibit the fracture deflection and cause a narrower width of fracture. The effect of Poisson’s ratio on fracture aperture is less than 1 mm. When perforation angle is perpendicular to maximum horizontal principal stress, the fracture width first increases rapidly and then gradually decreases from heel to tip. The influence degree of each factor on fracture deflection is ranked: stress difference of in-situ stress is the biggest, followed by injection pressure and perforation angle. This study is of great significance for the control of hydraulic fracture morphology and the further improvement of fracturing effect.